The Motivation of Crossfit Practitioners for Competition - NEGREA, Cristian; CHIOSEA, Amelia; ARSENI, Nada; PETRACOVSCHI, Simona; ARNAUTU, Gabriel (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
CrossFit is an emerging trend that has captured the attention of many studies in recent years. Despite the high number of research papers covering different aspects of the sport, the motivation of participants in CrossFit competitions remains a topic that is not talked about enough. The purpose of this study is to analyze how competition influences the motivation of CrossFiters. We applied a questionnaire who contains a number of 27 items on a 5-point Likert scale to observe how the participants’ motivation influences their view on the competition. The results indicate that all four variables used to define the motivation of competitors (enjoyment to compete, self-perception, challenges, CrossFit community) are significant, while loss of motivation is not a significant factor. Regarding gender, there is a significant difference between the groups in terms of CrossFit community perception (p< 0.05). In conclusion, competitive experience plays a crucial role in self-perception, competitive satisfaction, and appreciation of the CrossFit community.